Work Family Conflicts: Private Lives ― Public Responses - Rosenfeld, Mark (Labour / Le Travail, 1992)
The article reviews the book, "Work Family Conflicts: Private Lives ― Public Responses," by Bradley K. Googins.
Keywords: BOOKS – Reviews; GOOGINS; Bradley K.; Nonfiction; SOCIAL problems; WORK Family Conflicts: Private Lives: Public Responses (Book)